HPV vaccine, Twitter, and gay, bisexual and other men who have sex with men. (21st April 2019) - Budenz, Alexandra; Klassen, Ann; Leader, Amy; Fisher, Kara; Yom-Tov, Elad; Massey, Philip
Abstract: This study aimed to quantify human papillomavirus (HPV) vaccine Twitter messaging addressing gay, bisexual and other men who have sex with men (GB+MSM) and describes messaging by vaccine sentiment (attitudes towards vaccine) and characteristics (topic of messaging). Between August 2014 and July 2015, we collected 193 379 HPV-related tweets and classified them by vaccine sentiment and characteristics. We analysed a subsample of tweets containing the terms 'gay', 'bisexual' and 'MSM' ( N = 2306), and analysed distributions of sentiment and characteristics using chi-square. HPV-related tweets containing GB+MSM terms occupied 1% of our sample. The subsample had a largely positive vaccine sentiment. However, a proportion of 'gay' and 'bisexual' tweets did not mention the vaccine, and a proportion of 'gay' and 'MSM' tweets had a negative sentiment. Topics varied by GB+MSM term—HPV risk messaging was prevalent in 'bisexual' (25%) tweets, and HPV transmission through sex/promiscuity messaging was prevalent in 'gay' (18%) tweets. Prevention/protection messaging was prevalent only in 'MSM' tweets (49%). Although HPV vaccine sentiment was positive in GB+MSM messaging, we identified deficits in the volume of GB+MSM messaging, a lack of focus on vaccination, and a proportion of negative tweets. While HPV vaccine promotion has historically focused on heterosexual HPV transmission, there are opportunities to shape vaccine uptake in GB+MSM through public health agenda setting using social media messaging that increases knowledge and minimizes HPV vaccine stigma. Social media-based HPV vaccine promotion should also address the identities of those at risk to bolster vaccine uptake and reduce the risk of HPV-attributable cancers.